2008
DOI: 10.1097/brs.0b013e31816043d1
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Wrong Level Surgery Among Spine Surgeons

Abstract: There is a high prevalence of wrong level surgery among spine surgeons; 1 of every 2 spine surgeons may perform a wrong level surgery during his or her career. Although all spine surgeons surveyed report using at least 1 preventive action, the following measures are highly recommended but inconsistently adopted: direct preoperative communication with the patient by the surgeon, marking of the intended site, and the use of intraoperative verification radiograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 23 publications
3
149
0
2
Order By: Relevance
“…A recent questionnaire study by Mody et al 12 found a high prevalence of wrong-level surgeries among spine surgeons with nearly 50% of surgeons performing a wrong-level surgery during their career. Correct-level spine surgery is an important patient safety and quality-of-care issue.…”
mentioning
confidence: 99%
“…A recent questionnaire study by Mody et al 12 found a high prevalence of wrong-level surgeries among spine surgeons with nearly 50% of surgeons performing a wrong-level surgery during their career. Correct-level spine surgery is an important patient safety and quality-of-care issue.…”
mentioning
confidence: 99%
“…Half of the surgeons reported that they had done 1 or more wrong level surgeries during their career (14). As this is a self-reported study and retrospective in nature, it is inferred that this is likely an underestimate of the true incidence of incorrect spine level localization.…”
Section: Discussionmentioning
confidence: 78%
“…Mody et al, conducted a survey of members of the American Academy of Neurologic Surgeons which showed that 15% reported that, at least once, they had prepared the incorrect spine level, but noticed the mistake before making the incision (14). Half of the surgeons reported that they had done 1 or more wrong level surgeries during their career (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2003 confidential survey, 16 % of hand surgeons reported that they had prepared to operate on the wrong site but then noticed the error prior to incision (nearmiss), and 21 % reported that they had actually performed wrong-site surgery at least once during their careers [21]. Worse, in a 2008 study, 15 % of spine surgeons reported that they had prepared the incorrect spine level at least once and noticed the mistake before making incision (near-miss), but a full 50 % had performed one or more wrong-level surgeries during their career [22]. By way of analogy, the aviation community would have to experience every other pilot landing at the wrong airport at least once in their careers; this obviously does not occur in this high reliability industry.…”
Section: Other Specialties' Challengesmentioning
confidence: 99%